A Comparative Study on Green Banking Initiatives of SBI & ICICI Bank - Punit Kumar Kanujiya, Pooja Dubey (Journal of Informatics Education and Research, 2024)
Global warming and other environmental damage have grown to be serious concerns as a result of increased industrialization. It is a worldwide concern rather than a personal economic issue, and the only way to see rapid economic growth is for all industries to play a part in maintaining a sustainable environment. Banks can make a significant contribution to a greener and create more sustainable environment. Green banking is the practice of conducting standard banking operations with environmentally friendly technology. Environmentally conscious banking has gained popularity across the globe in the last few decades. India is also making every effort to support banks who adhere to environmental responsibility. The purpose of this article is to present a thorough comparative analysis of the green banking efforts implemented by two renowned Indian banks: SBI & ICICI Bank. According to the study, Indian banks now provide more services than only internet banking, such as waste management, carbon neutralization, support for green projects, and other pertinent areas. It has been suggested that more green banking activities should be promoted in India so that a variety of small banks can also significantly contribute to green banking. The outcomes of the study may assist regulatory organizations, including banks, assess how much green banking in India has room to develop.